ASSESSMENT OF QUALITY OF LIFE IN PATIENTS OF TYPE 2 DIABETES MELLITUS USING THE DIABETES 39 QUESTIONNAIRE - Rajgopal, Jayesh K.m. (Innovare Journal Health Sciences, 2016)
Abstract Objective: The objective of this study is to assess the quality of life using the D39 questionnaire in the patients of type 2 diabetes Mellitus. Methods: A Cross sectional study was performed in the outpatient department. The study population was consisted of 160 type 2 diabetes mellitus patients attending the OPD. This study was carried out for a period of 3 months. Results: Our study showed a total of 93 males (58.13 %) and 67 females (41.88 %). Mean age in our study was 48.72 ± 8.17 years. Mean duration of diabetes in our study was 5 ± 3.06 years. Our study shows that 61(38.12 %) has hypertension as a co-morbidity, 28(17.5 %) has hyperlipidaemia and 2(1.25 %) has renal dysfunction. The Diabetes 39 (D-39) Instrument Evaluation, containing five dimensions: energy and mobility (15 items), diabetes control (12), anxiety and worry (4) social overload (5) and sexual behaviour (3), was used. Discussion: This study demonstrated that the quality of life in patients of diabetes is clearly affected by the complication and comorbidities associated with type 2 diabetes. Longer studies are needed to completely assess the quality of life. Key Words: Type 2 Diabetes Mellitus, Quality of life, D39 Questionnaire.